Micromanaging atherosclerosis: myeloid cell-specific microRNA-26b attenuates atherosclerosis development. (10th June 2022) - Peters, L; Bidzhekov, K; Jansen, Y; Bayasgalan, S; Gencer, S; Sundararaman, SS; Bonnin-Marquez, A; Yan, Y; Jans, AM; Bartneck, M; Doering, Y; Weber, C; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Increasing evidence has shown that microRNAs (miRs) are fundamental players in atherosclerosis, but the exact role of various miRs remains elusive. Preliminary data showed that, with a 5-fold increase, miR-26b was the most highly expressed miR in human atherosclerotic plaques compared to healthy vessels. Therefore, we aimed to determine its cell-specific effects on atherosclerosis development. We examined the role of miR-26b in atherosclerosis by using full-body knockout (KO) mice on a 4 weeks and 12 weeks Western type diet (WTD) and myeloid cell-specific miR-26b KO (LysM-Cre) mice on 12 weeks WTD on an apolipoprotein E-deficient background. Atherosclerotic plaque size and phenotype were analyzed via immunohistochemical and immunofluorescent stainings. The phenotype and function of bone marrow-derived macrophages (BMDMs) from full body KO mice were analyzed via PCR, ELISA and gelatinase assays. Lipid nanoparticles (LNPs) served as vehicles for miR-26b mimics to restore miR-26b levels in knockout BMDMs. A full-body miR-26b-KO on a 12 weeks WTD resulted in a striking 3.5-fold increase in atherosclerotic lesion size, compared to control. Consistent with a more advanced plaque phenotype, collagen content, smooth muscle cell percentage and relative necrotic core area were all significantly increased in plaques from miR-26b KO mice whilst the relative macrophage content was significantly reduced. Interestingly, the full-body KO mice on a 4 weeks WTD showed a remarkable 10-fold increase in plaque size and the respective plaques also had a reduced macrophage percentage, showing that miR-26b has very strong effects on both atherogenesis as well as atherosclerosis progression. Intriguingly, relative plaque size in the arches of miR-26b LysM-Cre mice were increased by 3-fold and collagen content was also increased significantly, suggesting a role for myeloid-specific miR-26b in atherosclerosis development. Further highlighting its myeloid-specific effects, miR-26b KO BMDMs showed an increase in IL-6 and TNFα secretion, which could be rescued by LNPs containing miR-26b mimics. Additionally, these miR-26b KO BMDMs showed a reduction in collagen breakdown. Overall, our results clearly demonstrate an atheroprotective role of myeloid cell-specific miR-26b by attenuating lesion initiation as well as progression, mainly by suppressing inflammation and stimulating collagen breakdown. Our study leads to exciting new insights into the role of miR-26b in atherosclerosis development, providing an important back-bone for future research and potential new treatment options.